The Role of Employee Motivation on The Relationship Between HRM Practices and Service Quality in Healthcare Organization - Totok Sasongko (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2018)
The human resources management in the healthcare institution is essential to enable the delivery of efficient and effective medical services. This study conducted to investigate how HRM practices  can enhance service quality and proposes an integrated framework in which perceived HRM practices are related to employee commitment, which in turn related to perceived service quality performance. Five HRM practices was selected. A questionnaire was constructed. The quantitative methodology was applied to collect and analyze data. Data was collected from 270 employees (including nurse and doctor) and bottom manager in  Dr. Radjiman Wediodiningrat in Indonesia. The result shows that the selected HRM practices all significantly and meaningfully can predicted the employee motivation, in which feedback and recogniton was the most effective practices. The result also shows that employee motivation is an effective predictor of service quality performance. Lastly, employee motivation has a role as mediator effect toward the relationship between HRM practice and service quality. This research suggests that HRM departement need to chooses human resources management practices properly that can increase employe motivation and their service quality performances.